1993
DOI: 10.1111/j.1600-0560.1993.tb01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of cutaneous T‐cell lymphoma for human herpesviruses by using the polymerase chain reaction

Abstract: The etiology of cutaneous T-cell lymphoma remains unknown, although an association with viral infection, in particular certain retroviruses and human herpesviruses, has been suggested. The purpose of this study was to examine skin biopsies of cutaneous T-cell lymphoma for the presence of Epstein-Barr virus, herpes simplex virus type 1 and type 2, and human herpesvirus-6 by using the polymerase chain reaction. Lesional skin biopsies from 30 patients with cutaneous T-cell lymphoma were studied. Control specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…EBV-encoded small nonpolyadenylated RNAs (EBERs) were detected by in situ hybridization in mycosis fungoides (MF) 17 and CTCL. 18 On the other hand, PCR, revealed no EBV DNA in CTCL 19 and Angele et al 20 showed the absence of EBER in CTCL. EBER has not yet been functionally characterized.…”
mentioning
confidence: 99%
“…EBV-encoded small nonpolyadenylated RNAs (EBERs) were detected by in situ hybridization in mycosis fungoides (MF) 17 and CTCL. 18 On the other hand, PCR, revealed no EBV DNA in CTCL 19 and Angele et al 20 showed the absence of EBER in CTCL. EBER has not yet been functionally characterized.…”
mentioning
confidence: 99%
“…More widely in lymphoproliferative skin disorders, the possible role of HHV‐6 has been investigated in three other studies. Two studies concerned cutaneous T‐cell lymphoma (CTCL): the first one showed only one HHV‐6 positive sample out of 30 lesional tissue samples coming from CTCL (35) and the second one only one out of 92 MF (13). Kempf et al.…”
Section: Discussionmentioning
confidence: 99%
“…failed to show EBV positivity by PCR in 30 MF/SS subjects. 17 Iwatsuki et al . found no EBV positivity by PCR and ISH in 19 MF/SS subjects.…”
Section: Discussionmentioning
confidence: 99%